Prior exercise speeds pulmonary oxygen uptake kinetics and increases critical power during supine but not upright cycling - Goulding, R. P.; Roche, D. M.; Marwood, S. (Experimental Physiology, 2017)
Critical power (CP) is a fundamental parameter defining high-intensity exercise tolerance and is related to the time constant of phase II pulmonary oxygen uptake kinetics (tVO2). To test the hypothesis that this relationship is causal we determined the impact of prior exercise ("priming") on CP and tVO2 in the upright and supine positions. 17 healthy men were assigned to either upright or supine exercise groups, whereby CP, tVO2 and muscle deoxyhaemoglobin kinetics (t[HHb]) were determined via constant-power tests to exhaustion at four work-rates with (primed) and without (control) priming exercise at ~31%?. During supine exercise, priming reduced tVO2 (control: 54 ± 18 vs. primed: 39 ± 11 s; P < 0.001), increased t[HHb] (control: 8 ± 4 vs. primed: 12 ± 4 s; P = 0.003) and increased CP (control: 177 ± 31 vs. primed: 185 ± 30 W, P = 0.006) compared to control. However, priming exercise had no effect on tV?O2 (control: 37 ± 12 vs. primed: 35 ± 8 s; P = 0.82), t[HHb] (CON: 10 ± 5 s vs. PRI: 14 ± 10; P = 0.10), or CP (control: 235 ± 42 vs. primed: 232 ± 35 W; P = 0.57) during upright exercise. The concomitant reduction of tVO2 and increased CP following priming in the supine group, effects that were absent in the upright group, provides the first experimental evidence that tVO2 is mechanistically related to critical power. The increased t[HHb] suggests that this effect was mediated, at least in part, by improved oxygen availability.